Management and Follow-Up Practices of Women With Recurrent Stress Urinary Incontinence Following Transobturator Mid-urethral Synthetic Sling Procedure: A 6-Year Retrospective Monocentric University-Based Study - Huang, Yi; Chen, Zhengsen; Shen, Baixin; Shao, Yunpeng; Gao, Jie; Zhou, Yiduo; Margit, Fisch; Wei, Zhongqing; Ding, Liucheng (Frontiers in Surgery, 2021)
Purpose To evaluate the efficacy of management and follow-up practices in repeat retropubic mid-urethral synthetic sling (MUS) procedure after TOT/TVT-O failure and to clarify the possible aetiology of recurrent stress urinary incontinence Methods All patients underwent medical history, physical examination, urodynamic study, 1-hour pad test and pelvic ultrasound to assess: urethral mobility, sling location Pre and postoperative. We performed a retrospective review of 35 women who underwent TVT sling after a previous failed transobturator midurethral procedure with recurrent SUI between February 2012 and November 2018 at a single center. The efficacy of the procedure was assessed at each follow-up visit, scheduled at 3, 6 and 12 Months after primary procedure. Results Thirty-five patients were included with primary transobturator mid-urethral synthetic sling procedure. At the 6 months follow-up, 32（91.42%) patients were socially continent and negative. The transperineal ultrasound measurement results revealed that the BND values in the recurrent group were significantly higher than those in the control. recurrent stress urinary incontinence is multifactorial etiologies include poor surgical technique, the sling type, inappropriate sling position and inadequate sling tension. Conclusion Recurrent SUI is a multifactorial aetiological factor, a repeat TVT procedure after a failed transobturator synthetic mid urethral sling was shown to be effective.